PERLINDUNGAN SOSIAL ANAK KORBAN KONFLIK DI LEMBAGA KESEJAHTERAAN SOSIAL ANAK DI KABUPATEN DEMAK - Herlina Puji Astuti; Ellya Susilowati; Atirista Nainggolan (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2022)
This study aims to obtain an empirical description of the respondent's characteristics, fulfillment of basic needs, access to education services, health services, self-identity services, special protection services, and alternative care for conflict-affected children at the La Tansa Foundation, Cangkring B Village, Karanganyar District, Demak Regency. The aspects of child protection studied include: 1) respondent characteristics, 2) access to basic needs, 3) access to education services, 4) access to health services, 5) access to personal identity services, 6) access to special protection services, and 7) alternative care. . The method used in this research is quantitative research with descriptive method. Sources of data used are primary and secondary data sources. The sampling technique in this study was a census technique which was conducted on 15 respondents. Data collection techniques used are questionnaires, study documentation and observation. The measuring instrument used is the rating scale. The results showed that the social protection of children victims of conflict was in the moderate category. However, the special protection aspect had the lowest score. Therefore, the “Parenting Skills for Caregivers at La Tansa Foundation” program is proposed.